2017
DOI: 10.18632/oncotarget.15468
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib radiosensitizes head and neck squamous cell carcinoma cells by targeting cancer stem cells

Abstract: The dismal prognosis of locally advanced and metastatic squamous cell carcinoma of the head and neck (HNSCC) is primarily due to the development of resistance to chemoradiation therapy (CRT). Deregulation of Epidermal Growth Factor Receptor (EGFR) signaling is involved in HNSCC pathogenesis by regulating cell survival, cancer stem cells (CSCs), and resistance to CRT. Here we investigated the radiosensitizing activity of the pan-EGFR inhibitor afatinib in HNSCC in vitro and in vivo. Our results showed strong an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
(88 reference statements)
3
32
0
Order By: Relevance
“…Afatinib, by inhibiting the tyrosine kinase activity of EGFR, leads to the inhibition of the PI3K/Akt and RAS/Raf/ERK1/2 pro-survival pathways in both cell lines ( 51 ). By these means, afatinib also establishes a G 0 /G 1 cell cycle arrest, as demonstrated in previous studies in HNSCC ( 38 , 52 ). We also observed a dose-dependent cell-cycle arrest in the G 0 /G 1 phase after 24 h of afatinib exposure.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Afatinib, by inhibiting the tyrosine kinase activity of EGFR, leads to the inhibition of the PI3K/Akt and RAS/Raf/ERK1/2 pro-survival pathways in both cell lines ( 51 ). By these means, afatinib also establishes a G 0 /G 1 cell cycle arrest, as demonstrated in previous studies in HNSCC ( 38 , 52 ). We also observed a dose-dependent cell-cycle arrest in the G 0 /G 1 phase after 24 h of afatinib exposure.…”
Section: Discussionsupporting
confidence: 80%
“…Similar, an in vivo study highlighted that afatinib combined with gemcitabine had more significant antitumor effect than each drug used alone in a nasopharyngeal xenograft model ( 42 ). More recently, a study using both in vitro and in vivo models showed the interest of afatinib as a radiosensitizer in HNSCC cells by targeting cancer stem cells ( 38 ). Recently, it was also shown that afatinib maintained its cytotoxicity in cetuximab-resistant HNSCC cell lines ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Afatinib overcame intrinsic and acquired cetuximab resistance by inducing cell cycle arrest and thus, apoptosis. In preclinical trials, afatinib achieved a sensitization towards radiotherapy in HNSCC and pancreatic cancer cells [114,115].…”
Section: Afatinib (Gilotrif™)mentioning
confidence: 99%
“…The primary risk factors for oral cancer are betel nut chewing, smoking, alcohol consumption, human papillomavirus infection, and cell inflammation ( 1 , 4 ). Surgery, radiation therapy, and chemotherapeutic drugs are currently the preferred methods of treating oral cancer ( 4 , 5 ). Cisplatin, carboplatin, 5-fluorouracil, paclitaxel and docetaxel are the chemotherapeutic agents currently used to treat patients with oral cancer ( 6 9 ); however, they do not significantly improve survival rates.…”
Section: Introductionmentioning
confidence: 99%